Translation as intercultural communication : selected papers from the EST Congress, Prague 1995 - Snell-Hornby, Mary; Jettmarová, Zuzana; Kaindl, Klaus (Benjamins translation library, 1997)
This selection of 30 contributions (3 workshop reports, 27 papers from 14 countries) concentrates on intercultural communication in its broadest sense: themes vary from dissident translation under the Marcos dictatorship in the Philippines and translation as a process of power in the 3rd world context to drama translation and the role of the cognitive sciences in translation theory. Topics of current interest such as media interpreting, news translation, advertising, subtitling and the ethics of translation have a prominent position, as does the Workshop 'Contact as Conflict' which discusses t.